1969
DOI: 10.1152/ajplegacy.1969.216.6.1517
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal regulatory factors of salt excretion during renal venous pressure elevation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…The finding that extracellular volume expansion alters the renal response to changes in intrarenal pressures has also been reported by Wathen and Selkurt (20).…”
Section: Discussionsupporting
confidence: 73%
“…The finding that extracellular volume expansion alters the renal response to changes in intrarenal pressures has also been reported by Wathen and Selkurt (20).…”
Section: Discussionsupporting
confidence: 73%
“…Since changes in both renal arterial (10) and venous pressure (11) are known to affect tubular fluid reabsorption, it seemed important to examine whether acute TIVC constriction affects water excretion independent of these intrarenal hemodynamic alterations. In each Group I experiment performed in dogs undergoing a water diuresis, acute TIVC constriction diminished CO and caused an antidiuresis.…”
Section: Discussionmentioning
confidence: 99%
“…This seemed to be, to a certain extent, a reversible phenomenon as lowering of renal vein pressure immediately improved urine output and GFR 18 24. Other studies have also indicated that temporary renal vein compression results in reduced sodium excretion, increased renal interstitial pressure and reduced GFR 25 26…”
Section: Pathophysiologymentioning
confidence: 96%